IMPLEMENTATION OF THE NURSING THEORIES “NEED FOR HELP WIEDENBACH” AND “CONSERVATION LEVINE” IN NURSING CARE FOR PREGNANT WOMEN WITH PREECLAMPSIA - Indah Lestari; Noer Saudah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Preeclampsia is a leading cause of maternal death during pregnancy, childbirth, and postpartum. The consequences of preeclampsia include HELLP syndrome, cardiovascular disorders, lung, kidney, and liver failure, coagulopathy, placental abruption, and cerebral hemorrhage. The consequences for the fetus include Intra-Uterine Growth Retardation (IUGR) and Intra-Uterine Fetal Death (IUFD). A comprehensive approach is needed in providing nursing care to mothers with preeclampsia. The aim of this study was to apply Wiedenbach's